Morphometrics and biological characteristics of Pentalonia nigronervosa, the vector of Banana bunchy top virus, living on various Araceous plants species - Suparman, Suparman; Oktarida, Rafika; Hamidson, Harman; Arsi , Arsi (Jurnal Hama dan Penyakit Tumbuhan Tropika, 2023)
Banana aphid Pentalonia nigronervosa Coquerel (Hemiptera: Aphididae) is widely known as the main vector of Banana bunchy top virus (BBTV). It had been reported that banana aphid could live on alternative hosts belong to Family Araceae, and become important issue since Araceous plants are commonly found surrounding banana cultivations. Research had been conducted to study the morphometrics and biological characteristics of banana aphids living on various species of Araceous plants. The results showed that Araceous plant species could influence the morphometric and biological characteristic of banana aphids, indicated by the significant difference in some biological characteristics such as life cycle, life span, reproductive period, and fecundity. The average life span of banana aphids living on Araceous plants ranged from 22.80 to 47.90 days, it was shorter than the one that of lived on a banana plants. P. nigronervosa was able to develop a bigger colony when the aphid lived on Araceous plants, especially when they were transferred to Bogor taro where their fecundity reached 63 nymphs per female. Araceous plants also affected the morphometric of P. nigronervosa indicated by smaller size of the aphids, compared to those living on banana plant. The ability of banana aphid to live and reproduce in various Araceous plants would be beneficial to the development of control strategies of BBTV.